2017
DOI: 10.1111/bjir.12269
|View full text |Cite
|
Sign up to set email alerts
|

Are There Unexplained Financial Rewards for the Snakes in Suits? A Labour Market Analysis of the Dark Triad of Personality

Abstract: The Big Five personality test is used to generate psychopathy, narcissism and Machiavellianism scores using a large UK individual level micro data set. These scores show that high levels of narcissism and Machiavellianism can be associated with a higher incidence of employment in managerial occupations, whilst high levels of psychopathy is related to higher employment in the other services sector. The paper finds a wage premium to Machiavellianism that is largest at the 90 th percentile, over and above all pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…It is clear that these measures must yield different results compared to those where psychopathy is operationalized in a comprehensive and multidimensional manner (this is particularly relevant to the SD3 measure of psychopathy, which is often used in research and which, in fact, examines maladaptive or unsuccessful psychopathy in the light of accentuated impulsivity and vindictiveness). On the other hand, previous research has shown that the trait of Machiavellianism (which depicts manipulative and deceitful behaviour and is therefore similar to the factor of Ruthless Manipulation isolated in this study) is positively related to the amount of personal income (Lindley, 2018;Spurk et al, 2016). In sum, researchers should be very careful regarding the specific measure of psychopathy they use in their research, and interpret their findings in the light of the administered scale's content.…”
Section: Corporate Psychopathy: Overcoming the Incongruent Findingsmentioning
confidence: 58%
“…It is clear that these measures must yield different results compared to those where psychopathy is operationalized in a comprehensive and multidimensional manner (this is particularly relevant to the SD3 measure of psychopathy, which is often used in research and which, in fact, examines maladaptive or unsuccessful psychopathy in the light of accentuated impulsivity and vindictiveness). On the other hand, previous research has shown that the trait of Machiavellianism (which depicts manipulative and deceitful behaviour and is therefore similar to the factor of Ruthless Manipulation isolated in this study) is positively related to the amount of personal income (Lindley, 2018;Spurk et al, 2016). In sum, researchers should be very careful regarding the specific measure of psychopathy they use in their research, and interpret their findings in the light of the administered scale's content.…”
Section: Corporate Psychopathy: Overcoming the Incongruent Findingsmentioning
confidence: 58%
“…Some studies found that people high in narcissism exhibit a strong interest in being leaders early in their careers (Kowalski, Vernon, & Schermer, 2017; Lindley, 2018), so they proactively seek such positions in organizations (Campbell & Campbell, 2009). This interest is aided by their better hiring prospects during job interviews (Paulhus et al, 2013) in which, as replicated in our Study 2, participants high in narcissism tend to be evaluated more favorably (Campbell & Campbell, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This interest is aided by their better hiring prospects during job interviews (Paulhus et al, 2013) in which, as replicated in our Study 2, participants high in narcissism tend to be evaluated more favorably (Campbell & Campbell, 2009). This could be why people high in narcissism are much more likely to be employed as managers (Lindley, 2018). Narcissism is particularly effective in leadership occupancy within the Indonesian educational setting as examined in Study 1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations